Analisa Kekerasan dan Kekuatan Tarik pada ST 60 Pasca Hardfacing Welding dengan Variasi Kuat Arus Las dan Elektroda Rd 260 3,2 mm - Sutrisno, Sutrisno; Azmal, Azmal; Widagdo, Eko (Politeknik Negeri Pontianak, 2024)
Welding is needed to fill holes in castings, increase the hardness of the tool layer and equipment or worn components. Damage usually occurs on the wheel shaft of the truck that rubs against the bushing. The purpose of this study was to determine the effect of the hardfacing welding method with variations in current of 90 A, 110 A and 120 A using RD 260 electrodes measuring 3.2 mm on surface hardness and tensile strength. The method used was experimental, aimed at testing and comparing ST.60 material that was not hardfacing welded and hardfacing welded. The results of the study obtained the highest average hardness value in hardfacing welding with a current of 120 A of 202.89 HV, the lowest average hardness value in specimens without hardfacing welding was 97.1 HV and hardfacing welding with a current of 90 A obtained an average hardness value of 104.80 HV and hardfacing welding with a current of 110 A obtained an average hardness value of 112.37 HV. For the average value of tensile strength (σtrk) without hardfacing welding is 660.67 N/mm², the tensile strength in hardfacing welding decreases where for a current of 90 A it is 567.80 N/mm², a current of 110 A the tensile strength (σtrk) is 568.88 N/mm² and 120 A the tensile strength (σtrk) is 574.11 N/mm². This shows that the surface hardness increases with increasing current in hardfacing welding and the tensile strength value will decrease.